Investigation of the Morphology, Composition, and Structure of Dehydrated Sewage Sludge of a Pulp and Paper Enterprise - Terekhin, A. P.; Maryandyshev, P. A.; Brillard, A. (Solid fuel chemistry, 2024)
The composition, structure, and morphology of dehydrated sewage sludge, a by-product of pulp and paper production, were studied. The thermal characteristics of sewage sludge were investigated. An elemental analysis of the sewage sludge was carried out, the results of which revealed a large number of noncombustible elements (5.5%), including heavy metals (vanadium, chromium, nickel, zinc, and strontium), compared to other types of fuel. Thermogravimetric studies on the thermal decomposition of dehydrated sediment were carried out. The thermogravimetric and differential thermogravimetric curves were described, and the temperature ranges of drying, release of volatile substances, and combustion of coke residue were determined. Microscope photos showed that the particle size of the sediment varied from 0.5 and 350 nm, and amorphous flakes and crystalline inclusions were the main elements of its structure.